THE MEDIEVAL MONGOLIAN ROOTS OF Y-CHROMOSOMAL LINEAGES FROM SOUTH KAZAKHSTAN - Zhabagin, Maxat; Sabitov, Zhaxylyk; Tarlykov, Pavel; Tazhigulova, Inkar; Junissova, Zukhra; Yerezhepov, Dauren; Akilzhanov, Rakhmetolla; Zholdybayeva, Elena; Wei, Lan-Hai; Akilzhanova, Ainur; Balanovsky, Oleg; Balanovska, Elena (BMC, 2020)
Background: The majority of the Kazakhs from South Kazakhstan belongs to the 12 clans of the Senior Zhuz. According to traditional genealogy, nine of these clans have a common ancestor and constitute the Uissun tribe. There are three main hypotheses of the clans’ origin, namely, origin from early Wusuns, from Niru’un Mongols, or from Darligin Mongols. We genotyped 490 samples of South Kazakhs by 35 Y-chromosomal SNPs (single nucleotide polymorphism) and 17 STRs (short tandem repeat). Additionally, 133 samples from citizen science projects were included into the study. Results: We found that three Uissun clans have unique Y-chromosomal profiles, but the remaining six Uissun clans and one non-Uissun clan share a common paternal gene pool. They share a high frequency (> 40%) of the C2*-ST haplogroup (marked by the SNP F3796), which is associated with the early Niru’un Mongols. Phylogenetic analysis of this haplogroup carried out on 743 individuals from 25 populations of Eurasia has revealed a set of haplotype clusters, three of which contain the Uissun haplotypes. The demographic expansion of these clusters dates back to the 13-fourteenth century, coinciding with the time of the Uissun’s ancestor Maiky-biy known from historical sources. In addition, it coincides with the expansion period of the Mongol Empire in the Late Middle Ages. A comparison of the results with published aDNA (ancient deoxyribonucleic acid) data and modern Y haplogroups frequencies suggest an origin of Uissuns from Niru’un Mongols rather than from Wusuns or Darligin Mongols. Conclusions: The Y-chromosomal variation in South Kazakh clans indicates their common origin in 13th–14th centuries AD, in agreement with the traditional genealogy. Though genetically there were at least three ancestral lineages instead of the traditional single ancestor. The majority of the Y-chromosomal lineages of South Kazakhstan was brought by the migration of the population related to the medieval Niru’un Mongols. Keywords: Human genetics, Y-chromosome, Short tandem repeat, Single nucleotide polymorphism, Time to the most recent common ancestor, Kazakh, Mongol, Wusun
Keywords: Human genetics; Y-chromosome; Short tandem repeat; Single nucleotide polymorphism; Time to the most recent common ancestor; Kazakh; Mongol; Wusun